To the systematic position of Pterostichus (Petrophilus) magoides (Straneo, 1937) (Coleoptera: Carabidae) from the Altai Mountains - I.I. Kabak (Кавказский энтомологический бюллетень, 2022)
A little-known species from the Altai, Pterostichus (Petrophilus) magoides (Straneo, 1937), is redescribed on the base of type specimens and supplementary material. Its systematic position and distribution are discussed. New synonymy is established: Pterostichus magoides = Pterostichus (Petrophilus) tatianae E. Berlov, 1996, syn. n. Tis species is similar to P. magus (Mannerheim, 1825), sharing with it the external characters, especially the shape of pronotum. Pterostichus magoides difers from it in having a smaller size, the upper surface of the head without punctures, normally lacking the parascutellar pore on elytra, bisetose anal sternite in male, long apical lamella of the aedeagus and conformation of the endophallus.